Oxygen Vacancy-Rich Cobalt-Doped MnO2 Nanorods for Zn Ion Batteries - Chen, Xiaowen; Xu, Zihan; Guo, Sai; Sun, Bo; Li, Qijian; Meng, Qingkun; Wei, Fuxiang; Qi, Jiqiu; Sui, Yanwei; Cao, Peng (ACS applied materials & interfaces, 2025)
Improving electrical conductivity and increasing the active site are important directions for improving the technology of manganese-based cathode materials for zinc ion batteries (ZIBs). In this paper, cobalt-doped and oxygen-vacancy coupled MnO2 nanorods (Vo-CMO) were prepared by defect engineering and an ion doping strategy as cathode materials for rechargeable ZIBs. Oxygen vacancies can increase the defect density of the material and provide more migration paths for zinc ions, thereby increasing the electrochemical activity and improving the specific capacity. The introduction of cobalt can adjust the electronic structure of manganese oxide, change the Fermi level of the material, and promote the generation and transmission of charge carriers, thereby increasing the charge transfer rate and increasing the conductivity of the material. The synergistic effect among them can improve the diffusion kinetics of zinc ions, thereby increasing the capacity and cycle stability of the material. The Vo-CMO has better Zn2+ storage capacity of 295.6 mAh·g–1 at 0.1 A·g–1. The reaction mechanism of Vo-CMO material was H+/Zn2+ coinsertion through galvanostatic current intermittent titration (GITT) and ex situ experiments. In addition, the Vo-CMO material assembled the flexible quasi-solid ZIB. The synergistic effect of cobalt doping and oxygen vacancy can provide a new way to develop water-based ZIBs.